AC and Weekly Paclitaxel Improve Outcomes in TNBC - Parry, Nicola (MD Conference Express, 2014)
This article presents the 10-year results of a study comparing taxane type and schedule as a component of adjuvant chemotherapy in localized breast cancer. When administered after doxorubicin-cyclophosphamide, weekly paclitaxel and every-3-weeks docetaxel significantly improved outcomes in the entire study population, while weekly paclitaxel improved outcomes in triple-negative breast cancer.